Effect of grinding time on bismuth oxyhalides optical and morphological properties influence on photocatalytic removal of organic dye. (October 2022) - Keerthana, S.P.; Kowsalya, K.; Kumar, P. Senthil; Yuvakkumar, R.; Kungumadevi, L.; Ravi, G.; Velauthapillai, Dhayalan
Abstract: Herein, we reported the synthesis of BiOX (X = Cl, Br) with different grinding time like 15 min and 30 min to analyze the evolution of physiochemical properties and the morphological evolution. The structural, optical, vibrational properties were examined by standard characterization studies. The formation of bismuth oxyhalides were confirmed by XRD and Raman studies. The crystallite size was decreased as in 30 min grinded sample whereas there is an influence of crystal structure. BiOCl (15 and 30 min) samples expelled the nanoflake like structure with the flakes arranged to form a nanoflower morphology. On comparing BiOCl (15 min), there is high orientation of nanoflakes on BiOCl (30 min) sample. As explored in BiOBr (15 and 30 min) samples, the development of nanoplates were found. The growth of nanoplates was enhanced in the better way in BiOBr (30 min) than BiOBr (15 min). The grinding time has explored a great influence on morphology. The photocatalyst test for prepared photocatalysts was performed to reduce the RhB dye. The photocatalysts showed 74%, 97%, 98% and 99.8% for BiOCl (15 min), BiOCl (30 min), BiOBr (15 min) and BiOBr (30 min). The rate constant value obtained was 0.008, 0.011, 0.021, 0.033 and 0.068 min −1 . BiOBr (30 min) sample achieved higher rate constant value. The hierarchical nanostructures and narrow bandgap has made the samples to be a potential candidate to reduce the toxic pollutants with complete efficiency. Graphical abstract: Image 1 Highlights: BiOCl (15, 30 min) expelled nanoflake structure arranged to form nanoflower. A high orientation of nanoflakes on BiOCl (30 min) sample explored. BiOBr (15, 30 min) explored development of nanoplates. 74%, 97%, 98% and 99.8% efficiency revealed for BiOCl (15 min), BiOCl (30 min), BiOBr (15 min), BiOBr (30 min).